PENGARUH MANAJEMEN MODAL KERJA DAN KEBIJAKAN PIUTANG TERHADAP PROFITABILITAS PERUSAHAAN SUB SEKTOR OTOMOTIF DAN KOMPONEN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Putri, Fanny Aulia; Ibrahim, Mariaty (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
This study aims to examine the persial and simultaneous influence of working capital management and receivable policies on profitability. Where independent variable in this research is working capital management and receivable policy while dependent variable is profitability. The sample used is secondary data derived from the financial statements of automotive manufacturing companies & components listed on the Indonesia Stock Exchange (IDX) period 20010 until 2014This study uses secondary data from the company's financial statements. Samples and sampling using purposive sampling technique. Data analysis using multiple linear regression analysis, t test, F test, and test of coefficient of determination. Data analysis using multiple linear regression analysis with SPSS 20.The results of this study indicate that the variable of working capital management and receivable policy in persial (t test) does not affect the profitability of automotive sub-sector manufacturing companies & components listed in Indonesia Stock Exchange. The simultaneous test results (f) show no effect of working capital management variable and receivable policy on profitability at automotive sub sector manufacturing & component listed in Indonesia Stock Exchange.Keywords: Working Capital Management, Receivables Policy, and Profitability